A Travesty of British Justice? Appealing against Internment during the Second World War. (28th January 2019) - Henderson, David
Abstract : In late 1940, the Australian government established Aliens Tribunals and Advisory Committees to ensure that local internees could, if they desired, protest against their internment. Most historians argue that this system of appeals was fundamentally flawed. This general explanation has much to commend it. Even so, the widely‐condemned appeals system requires some contextualisation. This article examines the appeal against internment of one man, Henry Brose, but it also seeks to place the appeals system in the broader context of the Australian government's attempt to balance personal liberty and national security over the course of the Second World War. The purpose of such an approach is not to offer a revision so much as a re‐contextualisation of an appeals system that historians have correctly described as flawed. This article demonstrates that the initial appeals system was certainly undermined by a government motivated by concerns for national security rather than personal liberty. But it also argues that the ongoing attempts of the Australian government to improve and overhaul the appeals system, in the midst of prosecuting an extraordinarily complex global war, suggests a more nuanced story than the one — of hapless victims and travesties of British justice — that has traditionally been told.